Factors Affecting Islamic and Conventional Mutual Funds’ Returns. A Comparative Analysis of Different Classes of Funds in Pakistan - Ahmed, Imran (i-Proclaim, 2019)
This study aims to analyze and investigate the factors influencing returns of Islamic and conventional mutual funds in Pakistan. Furthermore, this study aims to investigate whether macroeconomic and systematic factors affect Shariah compliant Equity, Income and Assets allocation Mutual Funds differently as compared their conventional counterparts. Different statistical techniques like correlation and regression analysis were applied to study their effect. The study concluded that macro-economic factors have an impact on both conventional and Islamic mutual funds however their impact seems to be insignificant at large. Overall funds behaved negatively with discount rate, inflation and GDP, whereas positively with trade and market index. Apart from income funds that were affected positively with discount rate. Furthermore, income funds were not affected by market index.  Moreover, inflation and GDP that is usually backed by higher interest rates, also effects overall returns negatively. There was no significant difference in the behavior among the Islamic and conventional funds with respect to the above-mentioned factors. Lastly, there was high correlation among both the equity and asset allocation based mutual funds (both Islamic and conventional). It was also found that asset allocation funds had close resemblance to equity-based funds as compared to income-based funds in term of factors influencing their returns, which suggested that most of the asset allocation funds have more portion of equity as compared to debt and could be considered high risk. Hence, they seem to be against Modern portfolio theory Markowitz (1952) presuming it to be in a minimum level of risk.